Cardiovascular Diseases Prediction Using Machine Learning Algorithms - Shaikh, Rumana M (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A broad variety of health conditions are involved in heart disease. Several illnesses and disorders come under the heart disease umbrella. Heart disease forms include: In arrhythmia, abnormality of the heart rhythm. Arteriosclerosis, Hardening of the arteries is atherosclerosis. Via cardiomyopathy, this disorder causes muscles in the heart to harden or grow weak. Defects of the congenital heart, heart abnormalities that are present at birth are congenital heart defects. Disease of the coronary arteries (CAD), the accumulation of plaque in the heart's arteries triggers CAD. It's called ischemic heart disease occasionally. Infections of the heart, bacteria, viruses, or parasites may trigger heart infections. Heart diseases namely arrhythmias, coronary heart disease, heart attacks, cardiomyopathy will be detect using the proposed algorithm in this paper. Here I compared three algorithms namely Restricted Boltzmann Machines, Deep Belief Networks and Convolutional Neural Networks for electrocardiogram (ECG) classification for heart disease.